Erysipelas of the leg (cellulitis) in sub-Saharan Africa: A multicentric study of 562 cases - Bayaki Saka; Ahy Boubacar Diatta; Ousmane Faye; Boh Fanta Diané; Abdoulaye Sangaré; Pascal Niamba; Christine Mandengue; Léon Kobengue; Assane Diop; Fatimata Ly; Mame Thierno Dieng; Alassane Dicko; et al. (Our Dermatology Online, 2017)
Introduction: Erysipelas of the leg is a common and serious infection. We carried out this study aiming at describing the epidemiological and clinical characteristics, and assessing the risks factors associated with the local complications of erysipelas of the leg in sub-Saharan Africa. Methods: This was a prospective multicentric study carried out in the dermatology units of Hospitals located in seven sub-Saharan African countries during a period of 12 months. Patients aged 15 and above with a first episode of erysipelas of the leg were recruited. Results: In this study, 562 patients were recruited, having a mean age of 43.7±16.9 years and a sex-ratio (M/F) of 0.67. Patients infected on one leg were 562 while those infected with two were 27. Bullous forms of the disease were observed in 95 patients, while purpuric forms were observed in 167 patients. The existence of a point of entry (485 cases), obesity (230), lymph edema (130) and the use of bleaching agents (97) were the mains risk factors. Complications during the course of the infection such as necrotizing fasciitis (34 cases) and abscesses (63 cases) were observed. They were due to the use of antibiotics and non-steroidal anti-inflammatory treatments, and the use of cataplasm. Conclusion: This study reveals that existence of a point of entry, obesity and lymph edema, and the use of bleaching agents were the mains risk factors influencing the local complications of erysipelas of the leg. Necrotizing fasciitis and abscesses were influenced by the use of antibiotics and non-steroidal anti-inflammatory treatments, and the use of cataplasm.